Evaluation of bumetanide as a potential therapeutic agent for Alzheimer’s disease - Boyarko, Ben; Podvin, Sonia; Greenberg, Barry; Momper, Jeremiah D.; Huang, Yadong; Gerwick, William H.; Bang, Anne G.; Quinti, Luisa; Griciuc, Ana; Kim, Doo Yeon; Tanzi, Rudolph E.; Feldman, Howard H.; et al. (Frontiers in Pharmacology, 2023)
Therapeutics discovery and development for Alzheimer's disease (AD) has been an area of intense research to alleviate memory loss and the underlying pathogenic processes. Recent drug discovery approaches have utilized in silico computational strategies for drug candidate selection which has opened the door to repurposing drugs for AD. Computational analysis of gene expression signatures of patients stratified by the APOE4 risk allele of AD led to the discovery of the FDA-approved drug bumetanide as a top candidate agent that reverses APOE4 transcriptomic brain signatures and improves memory deficits in APOE4 animal models of AD. Bumetanide is a loop diuretic which inhibits the kidney Na-K-2Cl cotransporter isoform, NKCC2, for the treatment of hypertension and edema in cardiovascular, liver, and renal disease. Electronic health record data revealed that patients exposed to bumetanide have lower incidences of AD by 35-70%. In the brain, bumetanide has been proposed to antagonize the NKCC1 isoform which mediates cellular uptake of choride ions. Blocking neuronal NKCC1 leads to a decrease in intracellular chloride and thus promotes GABAergic receptor mediated hyperpolarization, which may ameliorate disease conditions associated with GABAergic-mediated depolarization. NKCC1 is expressed in neurons and in all brain cells including glia (oligodendrocytes, microglia, and astrocytes) and the vasculature. In consideration of bumetanide as a repurposed drug for AD, this review evaluates its pharmaceutical properties with respect to its estimated brain levels across doses that can improve neurologic disease deficits of animal models to distinguish between NKCC1 and non-NKCC1 mechanisms. The available data indicate that bumetanide efficacy may occur at brain drug levels that are below those required for inhibition of the NKCC1 transporter which implicates non-NKCC1 brain mechanisms, and/or peripheral mechanisms, for improvement of brain dysfunctions and memory deficits. Moreover, bumetanide blocks NKCC1 in cells outside the central nervous system, e.g. in epithelia and the immune system (peripheral mechanisms). Clinical bumetanide doses for improved neurological deficits are reviewed.Regardless of mechanism, the efficacy of bumetanide to improve memory deficits in the APOE4 model of AD and its potential to reduce the incidence of AD provide support for clinical investigation of bumetanide as a repurposed AD therapeutic agent.